Exercise mitigates high-fat diet-induced cardiac dysfunction via APOE genotype- and immune-dependent mechanisms: A photon-counting CT study in adult mice - Rohan Nadkarni; Alex J. Allphin; Darin P. Clark; Yi Qi; Zay Yar Han; Ketan B. Ghaghada; Alexandra Badea; Cristian T. Badea (PLoS ONE, 2025)
Background Cardiovascular dysfunction frequently accompanies aging and is often worsened by adverse lifestyle factors and genetic susceptibility. The apolipoprotein E ( APOE ) gene modulates susceptibility to cardiovascular disease, but how exercise and diet interact with APOE genotype remains insufficiently understood. We investigate the cardioprotective potential of exercise in humanized APOE -targeted replacement mice on control and high-fat diet, using photon-counting computed tomography (PCCT) and deep learning-based image segmentation. Methods This study included 251 male and female mice in mid-to-late life of APOE2 , APOE3 , and APOE4 genotypes with variation in humanized NOS2 ( HN ) mediated innate immune response, exercise status (exercised vs. sedentary) and diet (control vs. high-fat). Mice underwent in vivo cine cardiac PCCT imaging following contrast enhancement with liposomal iodine nanoparticles. Stroke volume, ejection fraction, and myocardial mass were derived from automated segmentation of cardiac structures using a 3D U-Net model. We assessed main and interaction effects of genotype, sex, HN status, age, exercise and diet using generalized linear models, while Mann-Whitney U tests assessed effects of exercise within stratified subgroups. Results Exercise was a significant predictor of improvement in several cardiac functional metrics with a large effect size. The interaction between exercise and diet was a significant predictor of reduced body mass and myocardial mass. Stratified analyses found that exercise improves cardiac functional metrics in APOE4 mice on both diets, and APOE3 mice primarily on control diet, while benefitting HN mice more than non-HN mice. Conclusions Voluntary exercise can partially rescue cardiac dysfunction induced by high-fat diet in adult APOE -targeted replacement mice, with benefits modulated by genotype, sex, and HN status. APOE4 and HN mice benefitted most from exercise. Contrast-enhanced PCCT combined with deep learning segmentation enables scalable, minimally invasive cardiac phenotyping and reveals interaction effects that are critical for designing precision lifestyle interventions in genetically at-risk populations.